There is more to attraction than meets the eye: Studying decoy‐induced attention allocation without eye tracking. (6th September 2022) - Marini, Marco; Sapienza, Alessandro; Paglieri, Fabio
Abstract: Context effects in decision making refer to any influence on options evaluation resulting from its relational properties with other available alternatives. Over the last 40 years, a large corpus of research showed that decision makers are sensitive to irrelevant options and tend to modify their preferences depending on choice architecture. The attraction effect is a well‐known example of context effect, which describes an increase in preferences for an option when a dominated alternative is inserted in the choice set. Sequential sampling models (SSM) interpret decision biases as the result of a dynamic comparative process between the available options that alters subjective values attribution. Recently, SSM received empirical support from eye‐tracking studies that documented a decoy‐dependent allocation of attention. In this study, we integrate previous process‐tracing results using a new hidden‐attribute protocol, in which decision makers have to explore products' attributes, keep in mind their values, and deliberately compare the options. This new methodology allows this study to offer additional evidence on the role of decoys in the dynamic process of choice. In a consumer‐choice task, the addition of an asymmetrically dominated decoy first focused the attention on the target during attributes exploration, which in turn led to an increase in the dominant option preferences at the choice stage. This suggests that adding irrelevant options affects the information sampling procedures, insofar as the comparative process is influenced by the dominance relationship of the alternatives. These results are consistent with past eye‐tracking studies and verify previous connectionist theories of the attraction effect.